Psychological Approach to Prevent Religious Radical Behavior in Children - Muniroh, Siti Mumun (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to analyze the prevention of religious radicalism behavior in children through a psychological perspective. The research results show that the educational process at Green School Early Childhood Education plays a role in preventing children's radical behavior. However, individual identity, the influence of the social environment, and family dynamics also play a key role in forming radical attitudes and behavior. The prevention of religious radicalism behavior at Green School Early Childhood Education is carried out by promoting religious pluralism education, which is tolerance, by involving various parties. The theoretical implication of this research is the importance of a psychology-based approach in designing effective prevention programs. Education that emphasizes empathetic understanding, openness and critical understanding of religion can reduce the risk of radicalization. This study also reveals that recognizing the signs and seeds of potential radicalism in children as well as suitable, fast, and appropriate intervention is an important part of the strategy to prevent radicalism in children. The contribution of this study encourages the understanding that psychological approaches can be used as an urgent tool to prevent religious radicalism in children, in order to create a more inclusive, tolerant, and peaceful society